2019
DOI: 10.1017/jfm.2019.528
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear hydroelastic waves on a linear shear current at finite depth

Abstract: This work is concerned with waves propagating on water of finite depth with a constant-vorticity current under a deformable flexible sheet. The pressure exerted by the sheet is modelled by using the Cosserat thin shell theory. By means of multi-scale analysis, small amplitude nonlinear modulation equations in several regimes are considered, including the nonlinear Schrödinger equation (NLS) which is used to predict the existence of small-amplitude wavepacket solitary waves in the full Euler equations and to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…It is noted that the translating speed c and the Bernoulli constant B are also unknowns and need to be determined together with η(ξ ). The detailed derivation of (3.41) can be found, for example, in Gao et al (2019). The pseudo-differential operator T is defined as…”
Section: Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noted that the translating speed c and the Bernoulli constant B are also unknowns and need to be determined together with η(ξ ). The detailed derivation of (3.41) can be found, for example, in Gao et al (2019). The pseudo-differential operator T is defined as…”
Section: Validationmentioning
confidence: 99%
“…Whether the middle layer will completely disappear depends on the bifurcation mechanism of hydroelastic solitary waves. More precisely, if the associated nonlinear Schrödinger equation is of focusing type at c min , indicating that hydroelastic solitary waves bifurcate from infinitesimal periodic waves (Gao et al 2019), then the vertical-transport layer will vanish as the wave speed reaches c min , but not vice versa.…”
Section: Solitary Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus the one parameter function γ(k * , Ω) ≡ γ * (Ω) defines whether the NLS is focussing type. From [48], it is found that γ * (0) ≈ −0.0067 and that γ * < 0 for Ω > Ω * and γ * > 0 for Ω < Ω * where Ω * ≈ −0.0076. From this we can conclude that for Ω < Ω * we expect solitary waves to bifurcate from the trivial state, whereas for Ω > Ω * they may bifurcate at finite amplitude (see the Ω = 0 case [47]).…”
Section: Nonlinear Schrödinger Equation and Virial Theorymentioning
confidence: 99%